Availability of the core components of the World Health Organization infection prevention and control strategies in health facilities in Southwestern Uganda: Implications for control of COVID-19. Issue 2 (June 2022) - Ssekitoleko, Richard; Seremba, Emmanuel; Waiswa, Florence; Nabawanuka, Doreen; Muyinda, Paul; Okware, Solome; Bodo, Bongomin; Woldemariam, Yonas Tegegn; Moore, Christopher C.
Summary: Background: Infection prevention and control (IPC) practices are required to prevent nosocomial infection by severe acute respiratory syndrome coronavirus 2. In low- and middle-income countries, where resources are often limited, IPC practices are infrequently assessed. Aim: To assess the availability of the core components of World Health Organization (WHO) IPC practices at health facilities in Southwestern Uganda. Methods: We assessed the availability of WHO IPC core components using a modified WHO IPC Assessment tool. We determined differences between government versus private ownership and by type of health facility. Findings: We assessed 111 of 224 (50%) health facilities in four districts. The most frequently achieved core component of IPC strategies was environmental cleanliness with 75 of 111 (68%) facilities scoring >85%. The most infrequently achieved core component of IPC strategies was personal protective equipment (PPE) with only one of seven (14%) hospitals and no other facilities scoring >85%. Of the 20 hospital or health center IV facilities, five (25%) received an overall score of >85% compared to only one of 91 (1%) health center II or III facilities (odds ratio [OR] 30.0 [95% CI: 3.27–274.99], p=0.003). Of the 73 government facilities, two (3%) received an overall score of >85% compared to five of 38 (13%) private facilities (OR 0.24 [95% CI: 0.04–1.37], p=0.11). Conclusion: Few facilities in four districts in Southwestern Uganda achieved >85% availability of WHO IPC core components. Provision of PPE in these facilities should be prioritized.